Peran Digital Marketing Dalam Menarik Minat Calon Donatur Untuk Berdonasi Di Yayasan Galang Bersama Kami - Ryan Agung Ramadhan; Maskuri Sutomo; Syamsul Bachri ; Risnawati Risnawati (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
yayasan Galang Bersama Kami Foundation is an Islamic philanthropic humanitarian organization that is engaged in empowering poor people who use digital marketing as an online medium to attract potential donors to donate. The aim of this research is to find out how important the role of digital marketing is in attracting potential donors to donate to yayasan Galang Bersama Kami Foundation. This research approach uses a qualitative approach, which aims to interpret the data that has been collected, so as to obtain a general and comprehensive picture of the actual situation. Data collection techniques through interviews and observation. The data analysis technique uses interactive data analysis techniques. The results of this research are that digital marketing has the potential to attract potential donors to donate because it is very efficient in disseminating information about what is needed and to whom the donations are distributed. This research emphasizes the important role of the right digital platform to promote programs being run by foundations that are in need of potential donors. Using company digital marketing can increase trust and attract potential donors to donate to yayasan Galang Bersama Kami Foundation by using elements in digital marketing such as content marketing, social media, websites, digital advertising, CRM systems.